Efektivitas Atraktan Recycled Water terhadap Peningkatan Angka Bebas Jentik: The Effectiveness of Recycled Water Attractants in Improving the Larvae-Free Index - Muh. Saleh; Nildawati; Wahid, Isra; Khaer, Ain; Rachmat, Muhammad (Perkumpulan Entomologi Kesehatan Indonesia, 2024)
The increasing cases of Dengue Hemorrhagic Fever (DHF) in Indonesia demands effective, affordable, and environmentally friendly vector control strategies. This study aimed to evaluate the effectiveness of recycled water-based attractants in improving the Larvae-Free Index (Angka Bebas Jentik/ABJ) compared to conventional water and brown sugar plus yeast attractants. The study was conducted over nine weeks in three hamlets with homogeneous environmental characteristics in Pangkep Regency, South Sulawesi. Simple ovitraps were used to attract gravid female mosquitoes, while ABJ was measured through the inspection of natural containers. The results showed that recycled water significantly increased ABJ, reaching 96.08% in the eighth week, higher than conventional water (53.03%) and brown sugar plus yeast (37.50%). One-way ANOVA revealed a significant difference among attractant groups (p = 0.000), and further analysis using the Post-hoc Tukey test confirmed significant differences between recycled water and the other two attractants. In conclusion, recycled water proved to be an effective attractant for diverting mosquito oviposition from natural containers to ovitraps, thereby increasing environmental ABJ. This method has potential as a practical, sustainable, and community-based solution for vector control in dengue-endemic areas.